Explaining the social nature of "spiritual education" in Islam; Based on the social dimensions of worship In the view of Ayatollah Javadi Amoli - Fatemeh Vojdani; Fatemeh Alipoor (اخلاق وحیانی, 2024)
For modern man, spirituality has become individualistic to a great extent; and is often considered an emotional and psychological need and brings peace, love and happiness to a person. But it seems that spiritual education in Islam has a social nature. In Islam, with regard to the authenticity of spirituality, all teachings seek to cultivate spirituality in humans, and make humans aware of the real and spiritual world; even the teachings related to physical affairs of humans. But in particular, worships in a special sense that directly form the man-God relationship, are considered to be one of the strongest methods of strengthening spirituality and they provide a large part of spiritual needs. Therefore, through explaining the social nature of individual worship, the social nature of spiritual education can be better understood. The purpose of the present research is to show that according to Ayatollah Javadi Amoli's view, even individual acts of worship are charged with social aspects, and in the most private relationships between man and God, a person comes to God with a collective identity. Based on qualitative content analysis of the two books Hikmat Ibadat and Danesh and Ravesh Bandagi, eight main components with a social theme for worship were obtained: being with the crowd, general love and benevolence and social ties, financial support for the needy section of the society, moral-social elimination of vice, social moral interaction, rightism and defending the right. and truth, defense of the country and political insight and global effort.